KOMPARASI KINERJA KEUANGAN PERUSAHAAN PERJALANAN WISATA SEBELUM DAN SAAT PANDEMI COVID 19 - Endang Afriyeni; Melly Apriandi (Politeknik Negeri Bengkalis, 2023)
The purpose of this study was to determine the financial performance of travel companies where the case study at PT. Bayu Buana Tbk before the Covid-19 pandemic (2018-2019) and during the Covid 19 pandemic and how to compare financial performance before and during the Covid 19 pandemic. This research is a descriptive analysis. Financial performance is assessed by analyzing the financial statements by analyzing the ratios of the financial statements. The results of this study found that the liquidity ratio proxied by the current ratio, cash ratio and working capital ratio to total assets at PT Bayu Buana Tbk was considered better during the pandemic. The solvency ratio proxied by the debt to assets ratio, debt to equity ratio and long-term debt to equity ratio showed better performance during the pandemic. The activity ratio proxied by accounts receivable turnover, fixed asset turnover and total asset turnover where Total Assets Turn Over and fixed assets turn over decreased during a pandemic while Receivable Turn Over increased during a pandemic. Profitability ratios proxied by net profit margin, return on assets and return on equity were considered better in the pre-pandemic period. the market ratio proxied by earnings per share is considered better in the pre-pandemic period. Keywords: Liquidity, Solvability, Activity, Profitability, Market